Pemanfaatan Bonus Demografi melalui Peningkatan Indeks Pembangunan Manusia di Sumatera Utara - Sugiharto, Sugiharto; Setiawan, Deny (Universitas Negeri Medan, 2015)
This writing aims to gain the picture of profile in using of demographic bonus through increasing Human Development Index in the North Sumatra Province. It focus on local policy in utilizing the demographic bonus through elevating Human Development Index on several sectors such as education, health, and economy. Education sector coverage two indicators following Adult Literacy Rate Index (Lit) and Mean Years of Schooling Index (MYS). The population in this research is the citizenâs age group of 15 and more due to in fact that there many student dropout from the age group. The limitation is required for gain the representative number which is represents the fact, considering that citizen age group lower than 15 is still in schooling or preparing to school so it not apropriate to relying the years of schooling. Health sector indicate the numbers of years of life whichÂ is hopefully can be enjoyed by the citizens in an area by entering information regarding annual birth rate and death rate (variable eâ), that assumed represents average of age of life and citizen healthy in their life. Economic sector (Proper Life Standard), the profile uses the average of the real per capita expenditure which is adjusted (adjusted real per capita expenditure) or purchasing power parity. Based on study of the three of human development index, can be obtained the data concerning the factual picture of local government profile in utilizing demographic bonus.